2021
DOI: 10.3390/nu13020309
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Related Quarantine Effect on Dietary Habits in a Northern Italian Rural Population: Data from the Brisighella Heart Study

Abstract: North of Italy was severely hit by the COVID-19 (Coronavirus disease 19) pandemic. This induced the government to adopt severely restrictive measures to reduce the contagion risk, forcing most of the population to stop working and from leisure activities, and to remain at home for several weeks. Our study aimed to evaluate the effect of COVID-related quarantine on smoking and dietary habits of a well-characterized northern Italian rural population. For this purpose, while lockdown restrictions were in place (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
83
2
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(110 citation statements)
references
References 23 publications
7
83
2
9
Order By: Relevance
“…Beyond the results of the individual studies, none of which can be considered exhaustive, similar overall effects on lifestyle were observed: the lockdown triggered a trend towards increased sedentariness and weight gain [ 17 , 18 , 19 , 20 , 21 ], which was often associated with unhealthy eating patterns [ 17 , 18 , 22 ] that were more characteristic of females [ 17 ], although greater care in choosing healthy foods was also observed [ 20 , 21 , 22 ]. Tobacco smoking may or may not have increased during lockdown [ 17 , 21 , 22 , 23 ], while the overall trend for alcohol consumption seemed to increase [ 17 , 22 ]. However, all the studies conducted on this theme show that, for each of the lifestyle components, there were individuals whose habits worsened but also those with resilient attitudes, i.e., capable of taking advantage of social isolation to improve their lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the results of the individual studies, none of which can be considered exhaustive, similar overall effects on lifestyle were observed: the lockdown triggered a trend towards increased sedentariness and weight gain [ 17 , 18 , 19 , 20 , 21 ], which was often associated with unhealthy eating patterns [ 17 , 18 , 22 ] that were more characteristic of females [ 17 ], although greater care in choosing healthy foods was also observed [ 20 , 21 , 22 ]. Tobacco smoking may or may not have increased during lockdown [ 17 , 21 , 22 , 23 ], while the overall trend for alcohol consumption seemed to increase [ 17 , 22 ]. However, all the studies conducted on this theme show that, for each of the lifestyle components, there were individuals whose habits worsened but also those with resilient attitudes, i.e., capable of taking advantage of social isolation to improve their lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…A similar proportion (46%) of the Galcian population from Spain also reported eating more than before the lockdown and 44% of the 1350 adults in the study reported weight gain 16 . A qualitative study from Ghana found similar eating behavior leading to weight gain during the lockdown 17 . This weight gain was more pronounced in people with pre-existing overweight/obesity 18 .…”
Section: Dietary Habitsmentioning
confidence: 94%
“…This weight gain was more pronounced in people with pre-existing overweight/obesity 18 . In richer households, staying home encouraged excessive use of unhealthy foods, such as processed and fast foods in many parts of the world 15,[19][20][21] . An Italian study reported an increased uptake of 'comfort foods' including chocolates and ice-creams used by participants to allay lockdown anxiety 15 .…”
Section: Dietary Habitsmentioning
confidence: 99%
“…Another important limitation was that we did not examine whether dietary choices differed between, before, and during the pandemic. A recent survey study from Italy revealed that respondents exhibited less healthy dietary choices during the pandemic than before, including but not limited to increased intake of simple sugar and sweets and decreased intake of legumes [ 26 ]. Thus, it is unclear whether possible health benefits related to a shorter eating time window and longer overnight fast, as observed in our study, might be offset by poor dietary choices during the pandemic.…”
Section: Discussionmentioning
confidence: 99%